URBAN HEAT ISLAND DI KOTA TANGERANG SELATAN - Agita Devi Prastiwi; Supriatna Supriatna; Rudy P. Tambunan; Mangapul Parlindungan Tambunan (Jurnal Geosaintek, 2022)
Abstract. The industrial revolution opened up opportunities in changing people’s lives from an agrarian economic activity to an industry-based economy so that many people mass produced the phenomenon of migration. In 2018, 55% of the world’s population live in urban areas and by 20150 this will increase to 70 percent (United Nations, 2019). Migration disturbs the heat energy balance in urban areas as compared to suburban or surrounding areas, resulting in a temperature difference phenomenon known as urban heat island (Sharma et al. 2019). South Tangerang is one of the districts adjacent to the city of DKI Jakarta which is known as the world’s big city so it has vulnerability as a migration destination. So it is necessary to conduct a study that can provide an overview of the future phenomena of the emergence of potential urban heat island (UHI) that can be used as mitigation of the impacts of climate changes. As a results, from 2004 and 2020 there was an increase 0,30C UHI Index. The UHI phenomenon that occurs in South Tangerang City is also a result of existing developments in DKI Jakarta for areas that are directly connected to DKI Jakarta, such as Pondok Karya, Pondok Betung, and Cirendeu will experience urban growth.